Spectroscopic, Analytical and Biological Properties of New Copper(II) Complexes of Antiviral Drug 2-Amino-1,9-dihydro-9-[(2-hydroxyethoxy)methyl]- 6H-purin-6-one (Acyclovir) - Golcu, Aysegul; Dolaz, Mustafa; Kocak, Berna; Demirelli, Havva; Kavak, Nusret; Tumer, Mehmet (Asian Journal of Chemistry, 2010)
Two new copper(II) complexes with the antiviral drug acyclovir (H2L) have been synthesized: the mononuclear complex [Cu(H2L)Cl2]· 1.5H2O and the binuclear one [Cu2(H2L)3(H2O)2Cl·5(H2O). The complexes have been characterized using elemental analysis, conductivity, atomic absorption, electronic, IR and mass spectra, magnetochemical and thermogravimetric methods. In the mononuclear complex [Cu(H2L)Cl2]·1.5H2O, copper(II) is coordinated bidentately with the N and O groups of a drug molecule forming a nearly square-planar structure of the type CuL, with a CuNO chromophore. In complex [Cu2(H2L)3(H2O)2Cl·5(H2O) each copper atom is coordinated with one N atom from one ligand, one oxygen atom from one ligand molecule which serve as bridges in the formation of the binuclear complex [Cu2(H2L)3(H2O)2Cl·5(H2O). In aqueous solutions, a binuclear violet complex [Cu2(H2L)3(H2O)2Cl·5(H2O) is formed with an square pyramid structure. Measurable antiferromagnetic interactions between the two paramagnetic Cu(II) centers are responsible for some interesting magnetic properties. Using the Job method, the compositions of these complexes were determined. Protonation constants of the acyclovir and stability constants of its Cu2+ complexes were determined by potentiometric titration method in 50 % methanol-water mixtures at 25.00 ± 0.02 ºC under nitrogen atmosphere and ionic strength of 0.10 M sodium chloride. It has been observed that acyclovir has two protonation constants. The divalent metal ion Cu2+ forms CuL2, Cu2H2L2 and Cu2L stable complexes with acyclovir. The voltammetric behaviour of the complexes were studied using cyclic voltammetric technique. Different parameters were tested to optimize the conditions for the characterization of the complexes. The dependence of current intensities and potentials on pH, concentration, scan rate, nature of the buffer were also investigated. The antimicrobial activity studies of the acyclovir and it's complexes have been studied against some gram positive species: (Corynebacterium xerosis, Bacillus brevis, Bacillus megaterium, Bacillus cereus, Mycobacterium smegmatis, Staphylococcus aureus, Micrococcus luteus, Enterococcus faecalis) and gram negative (Pseudomonas aeruginosa, Klebsiella pneumoniae, Escherichia coli, Yersinia enterocolitica, Kluyveromyces fragilis, Saccharomyces cerevisiae, Candida albicans) bacteria.